lmprovement of methanol extract of Melia azedarach by some additives against Aphis fabae Scop. (Bollettino di zoologia agraria e bachicoltura, 2024)
The aphicidal effect of methanol extract of Melia azedarach L. against 2nd and 4th nymphal instars of A. fabae was evaluated. Although this extract may not be as effective as the synthetic insecticides, yet its effect can be enhanced by the use of suitable additives. The different additives used increased the toxicity of the crude extract. The most promising formulation used was methanol extract of M. azedarach + sesame oil. Addition of CaCl2 or MnCl2 to this formulation did not improve it, but, on the contrary, they had an antagonistic effect evidenced by lesser percentage of mortalities.In choice tests, high concentration of methanol extract exhibited a high degree of deterrence, for the adults larviposited very few number of young in comparison to those landed on control plants. Addition of different additives showed various effects. Methanol extract + DMSO exhibited a stimulant effect, where more young were larviposited on treated plants in comparison to the control. On the other hand, all the other formulations tested had a deterrent effect.
Keywords: Aphis fabae; Melia azedarach; methanol extract; additives